Attending a Biopsychosocially Focused Buprenorphine Training Improves Clinician Attitudes - Russell, Holly Ann; Smith, Brian; Sanders, Mechelle; Loomis, Elizabeth (Frontiers in Psychiatry, 2021)
Objective Substance use disorders remain highly stigmatized. Access to medications for opioid use disorder is poor. There are many barriers to expanding access including stigma and lack of medical education about substance use disorders. We enriched the existing, federally required, training for clinicians to prescribe buprenorphine with a biopsychosocial focus in order to decrease stigma and expand access to medications for opioid use disorder. Methods We trained a family medicine team to deliver an enriched version of the existing buprenorphine waiver curriculum. The waiver training was integrated into the curriculum for all University of Rochester physician and nurse practitioner family medicine residents and also offered to University of Rochester residents and faculty in other disciplines and regionally. We used the Brief Substance Abuse Attitudes Survey to collect baseline and post-training data. Outcomes 140 training participants completed attitude surveys. The overall attitude score increased significantly from pre to post-training. Additionally, significant changes were observed in non-moralism from pre-training (M=20.07) to post-training (M=20.98, p<.001); treatment optimism from pre-training (M=21.56) to post-training (M=22.33, p<.001); and treatment interventions from pre-training (M=31.03) to post-training (M=32.10, p<.001). Conclusion Increasing medical education around Opioid Use Disorder using a Family Medicine trained team with a biopsychosocial focus can improve provider attitudes around substance use disorders. Enriching training with cases may improve treatment optimism and may help overcome the documented barriers to prescribing medications for opioid use disorder and increase access for patients to lifesaving treatments.